A novel amphiphilic motif at the C-terminus of FtsZ1 facilitates chloroplast division. Issue 1 (10th November 2021) - Liu, Xiaomin; An, Jinjie; Wang, Lulu; Sun, Qingqing; An, Chuanjing; Wu, Bibo; Hong, Conghao; Wang, Xiaoya; Dong, Suwei; Guo, Junhua; Feng, Yue; Gao, Hongbo
Abstract: In bacteria and chloroplasts, the GTPase filamentous temperature-sensitive Z (FtsZ) is essential for division and polymerizes to form rings that mark the division site. Plants contain two FtsZ subfamilies (FtsZ1 and FtsZ2) with different assembly dynamics. FtsZ1 lacks the C-terminal domain of a typical FtsZ protein. Here, we show that the conserved short motif FtsZ1 C arboxyl-terminus (Z1C) (consisting of the amino acids RRLFF) with weak membrane-binding activity is present at the C-terminus of FtsZ1 in angiosperms. For a polymer-forming protein such as FtsZ, this activity is strong enough for membrane tethering. Arabidopsis thaliana plants with mutated Z1C motifs contained heterogeneously sized chloroplasts and parallel FtsZ rings or long FtsZ filaments, suggesting that the Z1C motif plays an important role in regulating FtsZ ring dynamics. Our findings uncover a type of amphiphilic beta-strand motif with weak membrane-binding activity and point to the importance of this motif for the dynamic regulation of protein complex formation. Abstract : A type of membrane binding motif with weak membrane-binding activity at the C-terminus of FtsZ1 regulates FtsZ ring dynamics and chloroplast division.